The high burden of hospitalizations for primary EBV infection: a 6-year prospective survey in a French hospital. (November 2015) - Hocqueloux, L.; Causse, X.; Valery, A.; Jandali, J.-C.; Maitre, O.; Soin, C.; Buret, J.; Ouane, F.; Niang, M.; Mille, C.; Prazuck, T.; Guinard, J.; et al.
Abstract: Primary Epstein-Barr virus infection (PEI) is acquired increasingly later in life in developed countries, involving a growing number of adults. No studies have examined the effect of age on PEI. We conducted a prospective, single-centre, noninterventional survey to assess the clinical and economic effects of PEI care according to age. We included all serology-confirmed cases observed in all departments of a large regional hospital. Clinical and biologic data, therapeutics and costs of care were examined. Over a 6-year period, we included 292 subjects (148 children and 144 adults) with a median age of 15.4 years (range 9 months to 79 years). Adults were hospitalized more often (83% vs. 60%) and for longer periods of time (median 4 days vs. 2 days) than children (p ≤ 0.0001 for both). Two adults required a secondary transfer into the intensive care unit, although no children did. Typically, adults showed higher levels of activated lymphocytes and liver abnormalities. They also required the use of systemic corticosteroids more often (45% vs. 23%, p < 0.0001) and for longer periods of time (median 7 days vs. 3 days, p 0.02) than children. Overall, the costs were significantly higher for adults than for children (median, €1940 vs. €1130, p < 0.0001), mainly because of the frequency and duration of hospitalizations. Age increases the immune response and clinical severity of PEI, resulting in substantial additional costs for the community. Better recognition of the disease in adults could shorten the average length of hospital stay.